Achieving grid parity of offshore wind power in China–A comparative analysis among different provinces. (December 2021) - Tu, Qiang; Liu, Zhuoran; Li, Borui; Mo, Jianlei
Highlights: The LCOEs of offshore wind power in China are calculated. The learning rate of offshore wind power is estimated using learning curve method. The grid parity of offshore wind power in China's five provinces is assessed. Grid parity can be achieved earlier with carbon finance policy being introduced. Abstract: Achieving grid parity of offshore wind power in China has great implication for the future energy system transition and plays an important role in achieving its carbon-peaking and carbon–neutral targets. However, the pace to reach grid parity among different regions as well as the policy needed to achieve it may be different in view of the disparity in the resource endowment and economic and market conditions. In this work, we collect the data of 83 offshore wind power projects connected to the grid in the period of 2013–2020 in China, and we estimate the learning rates of offshore wind power technology using learning curve model. Then, the future LCOEs of offshore wind power are projected among different provinces. Further, by comparing the future LCOEs and the on-grid price of coal-fired power, whether and when, and under what conditions the grid parity can be achieved are assessed at the province level, and especially the carbon finance policy needed to achieve the grid parity is explored. Finally, the policy strategy aimed to achieve grid parity among different regions is proposed.